2013
DOI: 10.4049/jimmunol.1202595
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammatory Twitch as a General Strategy for Controlling the Host Response

Abstract: Allergic inflammation is a general host-defense mechanism for dealing with perceived foreign invaders. While most effort has been directed toward understanding how this response gets turned on, how it gets turned off again when no longer needed is just as important to an organism’s survival. We postulate that the control of the allergic inflammatory response is achieved via frequency modulation whereby a sequence of self-resolving events are repetitively invoked only so long as antigen is present. This leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 26 publications
(50 reference statements)
0
27
0
Order By: Relevance
“…We have tested the plausibility of this hypothesis at the alveolarcapillary interface in the lung using an agent-based computational model that enabled us to investigate both the spatial and temporal behaviors of the various cellular players involved (3,12). Following calibration against the experimental data of Tanaka et al (21), we showed that this model can mimic the dynamics of allergic inflammation in mice (12), supporting the notion that there is a natural finite timescale to the normal inflammatory response.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…We have tested the plausibility of this hypothesis at the alveolarcapillary interface in the lung using an agent-based computational model that enabled us to investigate both the spatial and temporal behaviors of the various cellular players involved (3,12). Following calibration against the experimental data of Tanaka et al (21), we showed that this model can mimic the dynamics of allergic inflammation in mice (12), supporting the notion that there is a natural finite timescale to the normal inflammatory response.…”
mentioning
confidence: 82%
“…A key corollary of the inflammatory twitch hypothesis is that there should exist a refractory period during which the capacity to reinstigate inflammation is suppressed, akin to the refractory period associated with muscle twitches and neuronal action potentials. We have tested the plausibility of this hypothesis at the alveolarcapillary interface in the lung using an agent-based computational model that enabled us to investigate both the spatial and temporal behaviors of the various cellular players involved (3,12). Following calibration against the experimental data of Tanaka et al (21), we showed that this model can mimic the dynamics of allergic inflammation in mice (12), supporting the notion that there is a natural finite timescale to the normal inflammatory response.…”
mentioning
confidence: 83%
See 3 more Smart Citations